Relationship Of Knowledge With Parents' Perceptions About Covid-19 Vaccination In Children In The UPTD Puskesmas Area Sri Padang Tebing Tinggi Year 2022 - Fitriani Fadillah (Science Midwifery, 2022)
Knowledge or cognitive is a very important domain for the formation of one's actions. With this knowledge, people will understand how to act to prevent COVID-19. The purpose of this study was to determine the relationship between knowledge and parents' perceptions of covid 19 vaccination in children in the UPTD area of the Sri Padang Tebing Tinggi Health Center in 2022. This research method used descriptive design (cross sectional), the population in this study were children who were vaccinated at the Sri Padang Cliff Health Center and the sampling technique used the accedental sampling technique, the number of samples was 36 people. The data analysis used was univariate analysis. and bivariate using chi-squaree test. The results obtained from 36 respondents showed that the majority had good knowledge while PParent's perception of COVID-19 vaccination in children is positive. Bivariately the results of the study showed that there was a relationship between knowledge and parents' perceptions of COVID-19 vaccination in children in the uptd area of the Sri Padang Cliff Public Health Center in 2022 which was marked by the statistical test results obtained p-value 0.000 < = 0.05. The conclusion in this study is that there is a statistically significant relationship between knowledge and parents' perceptions of covid 19 vaccination in children in the UPTD area of the Sri Padang Tebing Tinggi Health Center in 2022.